rs12537 Is a Novel Susceptibility SNP Associated With Estrogen Receptor Positive Breast Cancer in Chinese Han Population - Xu, Jingkai; Li, Guozheng; Chen, Mengyun; Li, Wenjing; Wu, Yaxing; Zhang, Xuejun; Cui, Yong; Zhang, Bo (Frontiers in Medicine, 2021)
Genetic testing is widely used in breast cancer and has identified a lot of susceptibility genes and single nucleotide polymorphisms (SNPs). However, for many SNPs, evidence of an association with breast cancer is weak, underlying risk estimates are imprecise, and reliable subtype-specific risk estimates are not in place. A recent genome-wide long non-coding RNA (lncRNA) association study in Chinese Han has verified a genetic association between rs12537 and breast cancer. This study is aimed at investigating the association between rs12537 and the phenotype. We collected the clinical information of 5,634 breast cancer patients and 6,308 healthy controls in the early study. And χ2 test was used for the comparison between different groups in genotype. The frequency of genotypic distribution among SNP rs12537 has no statistically significant correlation with family history (p = 0.8945), menopausal status (p = 0.3245) or HER-2 (p = 0.2987), but it is statistically and significantly correlated with ER (p = 0.004006) and PR (p = 0.01379). Most importantly, compared to the healthy control, rs12537 variant is significantly correlated with ER positive patients and the p value has reached the level of the whole genome (p = 1.66E-08 < 5.00E-08). Furthermore, we found rs12537 associated gene MTMR3 was lower expressed in breast cancer tissues but highly methylated. In conclusion, our findings indicate that rs12537 is a novel susceptibility gene in ER-positive breast cancer in Chinese Han population and it may influence the methylation of MTMR3.